CRRT Connected to ECMO: Managing High Pressures. Issue 1 (January 2017) - de Tymowski, Christian; Augustin, Pascal; Houissa, Hamda; Allou, Nicolas; Montravers, Philippe; Delzongle, Alienor; Pellenc, Quentin; Desmard, Mathieu
Abstract : Metabolic disorders and fluid overload are indications of continuous renal replacement therapy (CRRT) including continuous venovenous hemofiltration in patients on extracorporeal membrane oxygenation (ECMO). Direct connection of CRRT machine to the ECMO circuit provides many advantages. Nevertheless, because pressures in CRRT lines relate to ECMO blood flow, high ECMO blood flow may be associated with high pressures in CRRT lines. Thus, management of CRRT pressure lines becomes challenging. We evaluated a protocol for managing high CRRT pressures. Connections were performed according to a standardized protocol to maintain CRRT lines in the correct pressure ranges without modifying ECMO settings or inhibiting pressure alarms. To achieve this goal, the way of connecting of CRRT lines was adapted following a standardized protocol. Connection was first attempted between pump and oxygenator in the 12 patients. In five cases, high pressures in CRRT lines were successfully managed by changing the connection segment. Continuous renal replacement therapy parameters were within target levels and reduction of serum creatinine was 37%. In conclusion, management of high pressures in CRRT lines induced by ECMO could be achieved without modifying ECMO blood flow or inhibiting CRRT alarms. Iterative stops were avoided allowing efficient procedures.